The Effectiveness of “Gamilab” Media Online Games For Arabic Vocabulary Mastery at Junior High School - Muhammad Fajar; Miatin Rachmawati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study explains the effectiveness of teaching Arabic vocabulary mastery using Gamilab media online games, particularly at the junior high school level. The difficulty students face in learning is due to a lack of supportive facilities, which affects their motivation during lessons. This research employs a quantitative approach, with the experimental method used by the researcher. The experimental design follows the "pretest-posttest one group design."The population of this study consists of 80 students from Mts Muhammadiyah Muallimien Muallimat Jakarta. The sampling method used is purposive sampling, and the sample under investigation includes 25 eighth-grade students from Mts Muhammadiyah Muallimien Muallimat Jakarta, drawn from one class. The validity test results show that 20 (100%) of the pretest and posttest questions are valid. The reliability test, conducted using SPSS 26 with Cronbach's Alpha, yielded a coefficient of 0.733, indicating that the test instrument comprising 20 questions is reliable, as the alpha value exceeds the threshold of 0.70.Regarding difficulty levels, 60% of the questions were categorized as easy, while 40% were considered moderately difficult. In terms of item discrimination, 70% of the questions had a sufficient index, 30% had a good index, and 10% had a poor index. The normality test showed significance values of 0.194 and 0.68, both greater than 0.05, indicating that the data is normally distributed. However, a significance value of 0.43, which is less than 0.05, suggests that the data is not homogeneous. A significance value of 0.000 (less than 0.05) was obtained, further confirming this.The mean scores of the pretest and posttest showed an improvement from 47.40 to 74.00. Thus, it can be concluded that Gamilab media is quite effective in enhancing Arabic vocabulary mastery.